Bryopsis spp.: Generalities, Chemical and Biological Activities - Contreras, Neyder; Alvíz, Antistio; Torres, Jaison; Uribe, Sergio (Pharmacognosy Reviews)
Bryopsis spp, is a marine green algae distributed in tropical regions of worldwide which have been few studied a level of their chemical constitution and evaluation of properties of bioactive metabolites and derivatives with a high potential pharmacological in treatment of possible disease related with viral, fungi and bacterial diseases. Relevant information was selected from scientific journals, books and electronic reports employed database including PubMed, Science Direct, Scielo and Google Scholar. This review describe different aspects of the Bryopsis spp. such as general characteristics, some species found in tropical regions included in Colombia, metabolites derivatives and finally roles in the pharmacological activity with promissory application in drug discovery and therapies related with antitumoral, anti oxidant, antimicrobial, antiviral, anti-larvicidal, anticoagulant and antileishmanial. This review offers a new vision of the knowledge about of studies of product naturals and specifically in the investigations referred to Bryopsis spp. may be of great significance for the discovery of drugs for future treatments; thus may be generated new literature of natural elements and its potential drug target.
Keywords: Bryopsis spp; Activity; Algae; Metabolites